COMPARATIVE ANALYSE OF VAT SYSTEMS IN THE NEW EU MEMBER STATES - Maria Zenovia GRIGORE; Adina Julieta CĂLĂRĂȘANU (Challenges of the Knowledge Society)
The common system of value added tax plays an important role in the European single market, with VAT being a major source of revenue for Member States as well as for the EU budget. EU VAT legislation is constantly changing until a single EU VAT area is created. One of the most important objectives of the European Commission is to harmonise VAT rules in order to significantly reduce the €50 billion lost each year to VAT fraud in the EU, with the highest levels in the new Member States. Directive 2006/112/EC aims to apply common rules for Member States in the intra-Community area, while leaving each Member State free to decide, within certain limits, on the level of rates and ceilings, deductibility, time limits for declaration and payment, refunds, etc. The aim of the paper is to analyse the similarities and differences concerning VAT in the new Member States of the European Union. To this end, standard and reduced VAT rates, exemption thresholds for small businesses, the share of VAT in GDP and the VAT Gap in these countries are highlighted. The results of the study are a starting point for identifying the most appropriate solutions to improve VAT collection in Romania and the other EU-13 Member States.